Basic principles and current status of transcorneal and transscleral iontophoresis. (2nd September 2017) - Gratieri, Taís; Santer, Verena; Kalia, Yogeshvar N.
ABSTRACT: Introduction : Iontophoresis is an active non-invasive drug delivery technique that can increase the transport of charged and neutral molecules into and across biological membranes. Most research to-date has focused on (per)cutaneous iontophoretic drug delivery. However, recent studies illustrate its potential for drug delivery to the eye: corneal iontophoresis may enable targeted topical therapy of intracorneal diseases, whereas transscleral iontophoresis may enable non-invasive intraocular drug delivery. Areas covered : We describe iontophoretic principles in the context of ocular delivery before providing a summary of recent preclinical studies involving transcorneal and transscleral iontophoresis in vitro and in vivo . Subsequently, an overview of clinical applications with special focus on the transcorneal iontophoresis of riboflavin for corneal cross-linking and transscleral iontophoresis of corticosteroids for the treatment of posterior segment diseases is provided. Expert opinion : The feasibility of using iontophoresis for ocular drug delivery has been demonstrated. Drug formulation development and the ability to design iontophoretic applicators will now determine its success in the clinic. The specificities of the ocular globe must be taken into account; in particular, its unique morphology, and the smaller surface area available for drug diffusion and the fact that it is more susceptible to irritation and less robust than the skin.